الاستدلال بالأثر على الحجة اللغوية للقراءة القرآنية عند ابن خالويه - برناوي، محمد بن صالح بن زكريا (معهد الامام الشاطبي - مركز الدراسات والمعلومات القرآنية, 2022)
يدرس البحث الحجج اللغوية للقراءات القرآنية التي استدل لها ابن خالويه بالأثر، مع الإشارة إلى ثبوت الأثر المستدل به وعدمه. ويهدف البحث إلى التعرف على بعض مرجحات الحجج اللغوية للقراءات القرآنية، وقد سار البحث على المنهج الوصفي التحليلي. ومن أبرز النتائج: أن الأثر أحد الأدلة التي اعتمدها ابن خالويه لتقوية الحجة اللغوية، وتنوع الحجج اللغوية ما بين دلالية وصرفية ونحوية، وأكثر ما ورد -من الحجج- في البنية اسما كان أو فعلا، وقليل في الدلالة، والآثار المستدل بها على الحجة، منها: ما هو ثابت صحيح، وأكثرها غير ثابت. ومن توصيات البحث: دراسة الأدلة على الاحتجاج اللغوي -عند ابن خالويه- مجتمعة في عمل علمي واحد. This research studies Arabic linguistic evidences that ibn Khaalawayh used various narrations to establish Quran recitations (modes of reading the Quran), along with mentioned whether the narrations are authentic or not. The research aims to provide understanding about some of the reasons for particular linguistic evidences regarding to modes of recitation the Quran being given more importance than others. To do that, a descriptive analytical method has been used. Among the most noteworthy results: Narrations are among the proofs that ibn Khaalawayh depended upon for supporting linguistic evidences; the evidences are of various types, whether semantic, grammatical, or morphological; most evidences have to do with the construction of a single word, whether a noun or verb, and few are semantic; and some of the narrations used for supporting have authentic chains of transmission, but most don't have. One of the recommendations resulting from this research is to devote a single comprehensive work to studying the types of proofs that ibn Khaalawayh used for establishing linguistic evidences.
Keywords: القرآن الكريم -- النحو العربي -- القراءات القرآنية -- الاحتجاج اللغوي -- ابن خالويه، أبو عبدالله الحسين بن أحمد، ت. 980 م